Analogi Pesan Dakwah dalam Membangun Pemahaman Agama Terhadap Mad’u - Budi, Budi Firmansyah; Pipin Yosepin; Nurlaila Rais (AT-TAWASUL, 2024)
The development of social media in the digital era is increasingly rapid and offers many choices, making the da'wah process easier and faster to convey to the wider community. In this fast-paced and instant situation, preachers are required to be more creative, intelligent and interesting in delivering da'wah messages and ready to face various da'wah challenges. Dai must also be observant in choosing da'wah methods as a communication strategy so that da'wah messages are easily understood by mad'u, one of which is by using analogies. This study aims to determine the extent of the influence of the analogy of Gus Baha's preaching message on Youtube videos in building religious understanding of mad'u and what are the supporting and inhibiting factors of Gus Baha's preaching in building religious understanding of mad'u. This type of research is descriptive research with qualitative methods and phenomenological approaches. The research subject here is Gus Baha's video lectures on several Youtube accounts. The object of this research is the comments of the audience of Gus Baha's study in understanding the da'wah message conveyed. The data collection techniques are observation and documentation. The data analysis used is content analysis.The results of the study show that Gus Baha's method of da'wah analogy through Youtube is able to create a relaxed, entertaining atmosphere, the explanation is simple and easy to understand, so it is in great demand by the wider community.